Fermentasi: Metode untuk Meningkatkan Nilai Nutrisi Jerami Padi - Yanuartono, Yanuartono; Indarjulianto, Soedarmanto; Purnamaningsih, Hary; Nururrozi, Alfarisa; Raharjo, Slamet (Fakultas Pertanian Universitas Bengkulu, 2019)
Most of the ruminant livestock rations in Southeast Asia come from grain crops residues. Rice straw is the main crop residue which farmers usually store and use as ruminant feed in tropical areas especially during the long dry season whereby natural forages are being in constraint. However, feeding rice straw does not provide adequate nutrition for ruminants even for basic living because of its low nutritional value. The nutritional value of rice straw is limited by low levels of intake and slow digestibility and low levels of energy, protein, minerals and vitamins. Various types of treatments to improve the nutritional value of rice straw have been widely carried out including physical, biological and chemical methods. One of them is the fermentation technology that can improve the nutrition of rice straw. This review aims to describe the practical aspects of the fermentation process based on the results of previous study on rice straw to increase its nutritional value.